Diversity of soybean (Glycine max L.) genotypes based on agromorphological parameters - G. Beyene, Diriba; Jalata, Zerihun (Journal of Pure and Applied Agriculture, 2023)
Assessment of genetic diversity existing in breeding material is a key step in planning effective breeding programs. This experiment was carried out to discover the prevailing genetic variation among soybean genotypes for diverse characters for breeding. The study contained hundred soybean genotypes that were planted in a lattice (10 x10) design. The result confirmed that cluster IX (23) contained the widest variety of genotypes observed by means of cluster IV (22), cluster V (19), cluster III (12), and cluster I (10), while the minimum number of genotypes were clustered in cluster II and VII (1). Besides this, specific cluster combinations between cluster VI and IX, between III and VI had comparably higher intercluster distance (397.8) indicating the prescience of highly divergent genotypes suitable for direct variety development and/or hybridization to produce a wide array of desirable segregants. And the first four principal components having Eigen values extra than one accounted for 61.96% of the total version in soybean genotypes tested. The cluster method analysis discovered that cluster II and cluster VII contained suitable yield characters which can be useful to expand a variety through selection and/or source of genes for hybridization. Generally, our findings showed the existence of particularly divergent genotypes which may be promising either for direct variety development and/or hybridization for advanced soybean yield. © 2022 Department of Agricultural Sciences, AIOU